PERANCANGAN ANTENA MIKROSTRIP ULTRA WIDE BAND DENGAN MATERIAL TEKSTIL UNTUK APLIKASI WIRELESS BODY AREA NETWORKS - Amir, Ashadi (Department of Electrical Engineering, University of Patria Artha, 2019)
Ultra Wide Band (UWB) microstrip antenna designed using textile materials for Wireless Body Area Network (WBAN) applications is presented. The antenna consists of stairs patches and a ground plane with a dimension of 30 mm x 30 mm. Simulation is done by compared antenna performance using cotton, denim, felt and fleece materials. In this study, the parameters considered in the analysis process are the characteristics of S11 and gain value. Numerical evaluation based on simulation shows that the antenna performance well operated in the UWB frequency standard by FCC (3.1 - 10.6 GHz) with the bandwidth of ≥ 500 MHz. The use of felt material produces a wider bandwidth (3900 MHz). The fleece material provided a higher gain value on 6.51 dBi at the resonant frequency of 8.5 GHz.